ANALISIS KAUSALITAS HARGA BERAS, HARGA PEMBELIAN PEMERINTAH (HPP) DAN INFLASI SERTA EFEKTIVITAS KEBIJAKAN HPP DI INDONESIA - Andi Saputra; Bustanul Arifin; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This research aims to analyze the causal relationship between the retail price of rice (HEB) the government purchase price (HPP) and inflation in Indonesia. The data analysis used in this research is analysis of causality by using the Engel Granger causality analysis and analysis price  transmission elasticity. The results showed that there was one-way causality relationship between inflation and HEB. The HEB was at α=5% and the causality relationship between inflation and HPP were one-way.  Inflation affected HPP on both dry grain harvest (HGKP) and milled rice (HGKG) respectively - each at α=1%. There was one-way causal relationship between the retail price of rice and HPP. The HEB influenced HPP on both HGKP and HGKG at α=1% and α=5%. The HPP policy had not  been effectively done by price transmission elasticity between HEB, HGKP and HGKG which was equal to 0.9 (Et<1). It meant that changes in the level of consumer prices that occurred was not responded by the producer price level.Keywords: causality, HEB, HPP, HGKG, HGKP